2019
DOI: 10.1186/s12890-019-0928-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical associations of wheezes and crackles in the general population: the Tromsø study

Abstract: Background Wheezes and crackles are well-known signs of lung diseases, but can also be heard in apparently healthy adults. However, their prevalence in a general population has been sparsely described. The objective of this study was to determine the prevalence of wheezes and crackles in a large general adult population and explore associations with self-reported disease, smoking status and lung function. Methods We recorded lung sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 46 publications
(43 reference statements)
1
25
0
Order By: Relevance
“…Hearing crackles (any or basal) was not a significant independent predictor of COPD in the multivariable analysis, which may partly be explained by frequent occurrence of crackles among current smokers. 11 Wheezes were confirmed to be independent predictors of COPD. 21 ROC analyses showed that HF and COPD can be identified with similar ease based on history, symptoms, and signs.…”
Section: Main Findingsmentioning
confidence: 90%
See 3 more Smart Citations
“…Hearing crackles (any or basal) was not a significant independent predictor of COPD in the multivariable analysis, which may partly be explained by frequent occurrence of crackles among current smokers. 11 Wheezes were confirmed to be independent predictors of COPD. 21 ROC analyses showed that HF and COPD can be identified with similar ease based on history, symptoms, and signs.…”
Section: Main Findingsmentioning
confidence: 90%
“…Lung sounds were recorded at six locations of the chest, 15 s at each site, with a Sennheiser microphone inserted in the tube of a Littmann Classic II stethoscope. Presence of wheezes and crackles (also called rales or crepitations) during inspiration and expiration was determined by clinicians independently classifying the recordings blinded for other information; details on recording sites and classification of the sounds have recently been published 11 . Basal inspiratory crackles heard bilaterally were a category used in the analysis 17 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A patient with rheumatoid arthritis was likely to have interstitial abnormalities, increasing the prevalence of Velcro crackles. Also, age and smoking status may be factors associated with adventitious sounds [21]. Second, present cross-sectional design did not allow a comprehensive characterization of the study population and final clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%